(untitled) (Journal of Advanced Research in Social Sciences, 2024)
The political stability of a modern democracy, excluding environmental or external causes, is determined by multiple factors, all influenced by human behaviour. One indicator of political stability that takes the human factor into account is the time in office of a ruler. The stability of a ruler can be directly affected, for example, if they are killed, or indirectly, if the laws issued by the ruler are not followed. Non-compliance is dependent on the level of contempt for authority among citizens. A post-hoc hypothesis from a previous publication suggests that indigenous contempt for the authority of the white conqueror and coloniser is seen as a primary causal factor of political instability in Argentina. In this work, indigenous contempt has been shown to have originated from the mistreatment of indigenous peoples by the conqueror and coloniser, and it is expressed in practice by laws and norms being violated as a covert form of resistance. This behaviour has been spread throughout Argentine society due to extensive genetic mixing between Amerindian and Eurasian peoples, initially encouraged by the Spanish Crown. It is observed that these behaviours persist in the 21st century, partly because mistreatment and discrimination against indigenous peoples continue, and partly because pigmentocracy exists, a social system where wealth and status depend on skin colour. It is therefore crucial to understand that a large part of the causes of Argentina’s political instability can be traced to the non-compliance with laws and regulations, which originated as forms of indigenous resistance to the Spanish conqueror and coloniser. Public policies aimed at improving compliance should be designed to integrate indigenous cultures into Argentine identity, ensuring that all citizens wish to comply with the laws because they now see them as their own.